M83. AUTISTIC TRAITS AS LINKING PIN TO SOCIAL FUNCTIONING IN PSYCHOSIS: A NETWORK APPROACH. (18th May 2020) - Ziermans, Tim; Isvoranu, Adela-Maria; Schirmbeck, Frederike; Geurts, Hilde; De Haan, Lieuwe; ,
Abstract: Background: Both psychotic and autistic traits are related to poor social outcome in individuals with psychotic disorders (PD). However, it is unknown how specific trait clusters relate to each other and which are pivotal to social functioning. The aim of the present study was to use a network approach to address this issue and to investigate whether relations are similar in individuals with a familial risk for psychosis (FR) or typical comparisons (TC). Methods: The total sample consisted of 1413 individuals (504 PD, 572 FR, and 337 TC). Traits were assessed with the Autism Spectrum Quotient (AQ; 5 nodes) and the Community Assessment of Psychic Experiences (CAPE; 9 nodes). Social functioning was measured with the Social Functioning Scale (7 nodes). Results: Overall our results show that autistic traits are more negatively and closely related to social functioning, particularly in the interpersonal environment, than psychotic traits. These relations are more intrinsically connected for the PD network, as more and stronger connections between nodes were observed than for the FR and TC networks. In addition, the latter two networks appeared strikingly similar with only few unique relations. Discussion: Presence of autistic traits generally have a negative effect on social functioning, but in PD they may have a disproportional detrimental effect on psychopathology and levels of social functioning. These findings emphasize the need for increased clinical awareness of autistic comorbidity in psychotic patients to help enrich their daily social environments.